Imaging diamagnetic susceptibility of collagen in hepatic fibrosis using susceptibility tensor imaging. Issue 4 (21st October 2019) - Wei, Hongjiang; Decker, Kyle; Nguyen, Hien; Cao, Steven; Tsai, Tsung‐Yuan; Dianne Guy, Cynthia; Bashir, Mustafa; Liu, Chunlei
Abstract : Purpose: To characterize the magnetic susceptibility changes of liver fibrosis using susceptibility tensor imaging. Methods: Liver biopsy tissue samples of patients with liver fibrosis were obtained. Three‐dimensional gradient‐echo and diffusion‐weighted images were acquired at 9.4 T. Susceptibility tensors of the samples were calculated using the gradient‐echo phase signal acquired at 12 different orientations relative to the B0 field. Susceptibility anisotropy of the liver collagen fibers was quantified and compared with diffusion anisotropy, measured by DTI. For validation, a comparison was made to histology including hematoxylin and eosin staining, iron staining, and Masson's trichrome staining. Results: Areas with strong diamagnetic susceptibility were observed in the tissue samples forming fibrous patterns. This diamagnetic susceptibility was highly anisotropic. Both the mean magnetic susceptibility and susceptibility anisotropy of collagen fibers exhibited a strong contrast against the surrounding nonfibrotic tissues. The same regions also showed an elevated diffusion anisotropy but with much lower tissue contrast. Masson's trichrome staining identified concentrated collagens in the fibrous regions with high susceptibility anisotropy, and a linear correlation was found between the susceptibility anisotropy and the histology‐based staging. Conclusion: Diamagnetic susceptibility indicates the presence of collagen in the fibrotic liver tissues. Mapping magnetic susceptibility anisotropy may serve as a potential marker to quantify collagen fiber changes in patients with liver fibrosis.